1999
DOI: 10.1016/s0010-4655(99)00243-x
|View full text |Cite
|
Sign up to set email alerts
|

A program for coupled-channel calculations with all order couplings for heavy-ion fusion reactions

Abstract: A FORTRAN77 program is presented that calculates fusion cross sections and mean angular momenta of the compound nucleus under the influence of couplings between the relative motion and several nuclear collective motions. The no-Coriolis approximation is employed to reduce the dimension of coupled-channels equations. The program takes into account the effects of non-linear couplings to all orders, which have been shown to play an important role in heavy-ion fusion reactions at subbarrier energies. Distribution… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
840
1
10

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 903 publications
(858 citation statements)
references
References 15 publications
7
840
1
10
Order By: Relevance
“…The microscopic shell correction is adopted from the tabulated data of Möller et al [45]. Average values of l CN were calculated using the coupled-channel code CCFULL [53], but only small impact parameters and thus small angular momenta should contribute to the EvR cross sections because the higher partial waves result in almost certain fission during the de-excitation cascade.…”
Section: Model Calculationsmentioning
confidence: 99%
“…The microscopic shell correction is adopted from the tabulated data of Möller et al [45]. Average values of l CN were calculated using the coupled-channel code CCFULL [53], but only small impact parameters and thus small angular momenta should contribute to the EvR cross sections because the higher partial waves result in almost certain fission during the de-excitation cascade.…”
Section: Model Calculationsmentioning
confidence: 99%
“…However, the effects of coupling to excited states of the target and projectile can give rise to a distribution of Coulomb barriers with, in particular, some barrier "weight" at lower energies. With no coupling, the peak in the distribution of angular momenta occurs for L ≈ 8h, with a partial cross section of σ L ≈ 10 µb [33]. Coupled-channels calculations using the program CCFULL [33] figure 6(b) and the barrier distribution D = dT 0 /dE is shown in 6(c).…”
mentioning
confidence: 99%
“…With no coupling, the peak in the distribution of angular momenta occurs for L ≈ 8h, with a partial cross section of σ L ≈ 10 µb [33]. Coupled-channels calculations using the program CCFULL [33] figure 6(b) and the barrier distribution D = dT 0 /dE is shown in 6(c). We now see that the lowest barrier occurs at about 154.7 MeV, now below our incident energy.…”
mentioning
confidence: 99%
“…Broglia et al [29,30] suggested that the coupling to transfer channels with positive Q values is needed to explain the enhancement of fusion data for the Ni + Ni systems. Large enhancements of subbarrier fusion cross sections have been also observed in many other reaction systems with positive Q-value neutron transfer (PQNT) channels, such as the reaction systems 32 S + A Pd (A = 104-106, 108, and 110) [36], 40 Ca + 44,48 Ca [37], 40 Ca + 94,96 Zr [38,39], and 32 S + 94,96 Zr [40,41]. For some of these systems, the fusion excitation functions have been measured in sufficiently small energy steps, which can be used to extract the underlying barrier distributions to study the contribution from transfer channels.…”
Section: Introductionmentioning
confidence: 84%
“…Thus, the influence of the PQNT channels on fusion is accompanied by and depends on the change of nuclear deformations. In the quantum coupled channel (QCC) model [48], the coupling to PQNT channels is treated approximately by using a macroscopic form factor. Within the microscopic dynamics models, such as the quantum molecular dynamic model [49][50][51][52][53][54] and the time-dependent HartreeFock method [55][56][57][58][59][60][61], the effects of surface excitations as well as nucleon transfer can be automatically included.…”
Section: Introductionmentioning
confidence: 99%